Pengintegrasian Nilai-nilai Kearifan Lokal Masyarakat Adat Karampuang Dalam Pembelajaran Geografi Berorientasi Pendidikan Karakter Di Sekolah Menengah Atas - Syarif, Erman (LaGeografia, 2019)
The morality crisis is a problem in South Sulawesi, one of the efforts made by revitalizing local wisdom in learning in schools. The purpose of this study are: 1) analyzing the local wisdom values of the Karampuang indigenous people, and 2) integrating the values of local wisdom in learning geography. The approach used in this research is a qualitative case study. Collecting data by observation, interview and literature study. Data analysis procedures with data collection, data reduction, data presentation, and drawing conclusions. The results of the study show: 1) the local wisdom values of the Karampuang indigenous people are religious, care for the environment, love the motherland, work hard, be honest, be friendly, care socially and be responsible and friendly. 2) one of the applications of integrating the local wisdom values of the Karampuang indigenous people in learning geography in class XI on basic competencies 3.6 Analyzing the forms of local wisdom in agriculture, mining, industry, and tourism especially in the utilization of natural resources. Integrating the values of local wisdom is expected to create an educational system with quality human resources and character.